2019
DOI: 10.3389/fimmu.2019.00790
|View full text |Cite|
|
Sign up to set email alerts
|

Phagocytosis in the Brain: Homeostasis and Disease

Abstract: Microglia are resident macrophages of the central nervous system and significantly contribute to overall brain function by participating in phagocytosis during development, homeostasis, and diseased states. Phagocytosis is a highly complex process that is specialized for the uptake and removal of opsonized and non-opsonized targets, such as pathogens, apoptotic cells, and cellular debris. While the role of phagocytosis in mediating classical innate and adaptive immune responses has been known for decades, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
215
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(219 citation statements)
references
References 219 publications
(209 reference statements)
4
215
0
Order By: Relevance
“…Importantly, other research groups have suggested the proliferative and neurite-outgrowth properties exhibited by microglia represent a promising potential therapeutic target to repair injuries or treat degenerative disorders of affecting the central nervous system (CNS) 50 . This is consistent with their role during development, when dynamic patterns of morphological change during facilitate the formation of complex CNS and brain neuronal networks 51 , as well as their established roles in synapse monitoring 52 , apoptotic-debris clearing, and synaptic pruning 53 , all of which are required to maintain normal brain development and CNS homeostasis 54 . Microglia rapidly alter their morphology and function in response to changes in the brain microenvironment 55 .…”
Section: Discussionsupporting
confidence: 67%
“…Importantly, other research groups have suggested the proliferative and neurite-outgrowth properties exhibited by microglia represent a promising potential therapeutic target to repair injuries or treat degenerative disorders of affecting the central nervous system (CNS) 50 . This is consistent with their role during development, when dynamic patterns of morphological change during facilitate the formation of complex CNS and brain neuronal networks 51 , as well as their established roles in synapse monitoring 52 , apoptotic-debris clearing, and synaptic pruning 53 , all of which are required to maintain normal brain development and CNS homeostasis 54 . Microglia rapidly alter their morphology and function in response to changes in the brain microenvironment 55 .…”
Section: Discussionsupporting
confidence: 67%
“…Even more remarkably, the lifespan of a Harpegnathos individual is dramatically affected by changes in its social status, as the workergamergate transition results in a 5-fold increase in lifespan 24 . Given the importance of glia in protecting brains from the insults of time and disease [104][105][106][107] , we hypothesized that an expanded population of ensheathing glia in gamergates might contribute to their longer life expectancy and that the accelerated aging trajectory of workers might be accompanied by a change in the opposite direction.…”
Section: Gamergates Are Resistant To Aging-associated Decline In Enshmentioning
confidence: 99%
“…Notably, the inability to properly dispose of danger/damage-associated molecular patterns (DAMPs) such as protein aggregates, necrotic cells, and cellular debris has been shown to be a pivotal driver of both persistent and maladaptive immune activation in numerous neurological disorders [14,15]. In the case of CNS injury, inefficient removal of DAMPs has been proposed to perpetuate neuroinflammation and incite secondary CNS pathology and neurological complications [9,14,16,17]. However, we currently lack complete knowledge of the drainage pathways that the brain relies on to dispose of DAMPs and resolve tissue damage following TBI.…”
mentioning
confidence: 99%